Synthesis of Novel C2-Symmetric Sulfur-Based Catalysts: Asymmetric Formation of Halo- and Seleno-Functionalized Normal- and Medium-Sized Rings - Jana, Sadhan; Verma, Ajay; Rathore, Vandana; Kumar, Sangit (Synlett, 2019)
The synthesis of novel, highly functionalized, C2-symmetric sulfur-based catalysts is developed and their catalytic applications are explored in asymmetric bromo-, iodo- and seleno-functionalizations of alkenoic acids. This protocol provides the corresponding normal- and medium-sized bromo, iodo and selenolactones in up to 98% yield and 83% stereoselectivity.
Keywords: alkenoic acids; organosulfur catalysts; asymmetric catalysis; halolactones; selenolactones